Evaluation of hypolipidemic, antidiabetic and antioxidant activity of Eulophia herbacea tubers - Anil U. Tatiya; Pallavi M. Puranik; Sanjay J. Surana; Yogesh S. Patil; Rakesh E. Mutha (Bangladesh Pharmacological Society, 2013)
The tuber of Eulophia herbacea is widely used in the treatment of obesity in traditional medicine. Methanolic extract, aqueous extract and isolated gluco-mannan were tested for triton WR-1339 induced hyperlipidemia and alloxan-induced diabetes in rats. Blood samples were collected and analysed for lipid profile and blood glucose. Glucomannan was isolated and characterised. Antioxidant activity of test sample was determined by superoxide radical and lipid peroxidation assay and compared it with standards ascorbic acid. The findings showed that folk medicinal claim of E. herbacea tubers possess hypolipidemic, hypoglycemic and antioxidant effects.